(untitled) (Research, Society and Development, 2021)
Currently, the act of working is becoming more and more necessary in the lives of the majority of the population. People look for a way to meet their needs, which end up increasing over time. Citizens are aware that it takes a lot of effort to learn, work, and thus be an engaged professional future, completing their goals with wisdom and common sense, confident and doing enough to be efficient in their work, helping in the best way. possible in order to achieve a promising future. This article aims to present the benefits of a motivated professional to deal with the adversities of the current reality, based on bibliographic research. Its objectives are: to visualize the company’s quality of life as a motivation for professionals in the workplace. In conclusion, it is observed that an ideal environment and a safe professional form a good social life and leverage for a promising future.